Crossroads—Concerning Postmodernity and Organizations in the Third World: Opening a Debate and Suggestions for a Research Agenda - Alvarado, Felix (Organization Science, 1996)
A large part of writing concerning postmodernity has originated, either implicitly or explicitly, in “developed” countries. This includes both post-modern thought about issues of modernity and pre-modernity, and the discussion of post-modernity as an empirical “fact.” What first became apparent in art, literary criticism and philosophy has more recently affected our understanding of organizational phenomena. In this paper I intend to discuss some ramifications that postmodernity may have for the expansion of organizational theory, and more specifically for our understanding of organizations in contexts other than those of the United States and Western European and Far-Eastern industrial nations. The paper covers three aspects. First, it develops an account of my use of the concept of postmodernity as applied to organizations. Like other works in the field, for this I resort to the contrasting of modern and post-modern theories. Second, going beyond that well-trodden path, this paper includes an exercise in the application of the notion of the postmodern in organizations to contexts other than industrialized societies. Finally, drawing on the outcome of the exercise, it suggests some future key issues for inquiry, and a justification for a postmodern approach to the study of organizations in Third World contexts.